Hepatitis C virus pharmacogenomics in Latin American populations: implications in the era of direct-acting antivirals - Trinks J; Caputo M; Hulaniuk ML; Corach D; Flichman D (Dove Medical Press, 2017)
Julieta Trinks,1,2 Mariela Caputo,2,3 María L Hulaniuk,1 Daniel Corach,2,3 Diego Flichman2,4 1Basic Science and Experimental Medicine Institute (ICBME), University Institute of the Italian Hospital of Buenos Aires, 2Scientific and Technological National Research Council (CONICET), 3Servicio de Huellas Digitales Genéticas, Facultad de Farmacia y Bioquímica, 4Cátedra de Virología, Facultad de Farmacia y Bioquímica, Universidad de Buenos Aires, Buenos Aires, Argentina Abstract: In recent years, great progress has been made in the field of new therapeutic options for hepatitis C virus (HCV) infection. The new direct-acting antiviral agents (DAAs) represent a great hope for millions of chronically infected individuals because their use may lead to excellent cure rates with fewer side effects. In Latin America, the high prevalence of HCV genotype 1 infection and the significant association of Native American ancestry with risk predictive single-nucleotide polymorphisms (SNPs) in IFNL4 and ITPA genes highlight the need to implement new treatment regimens in these populations. However, the universal accessibility to DAAs is still not a reality in the region as their high cost is one of the major, although not the only, limiting factors for their broad implementation. Therefore, under these circumstances, could the assessment of host genetic markers be a useful tool to prioritize DAA treatment until global access to these new drugs can be achieved? This review will summarize the scientific evidences and the potential implications of HCV pharmacogenomics in this rapidly evolving era of anti-HCV drug development. Keywords: hepatitis C virus, pharmacogenomics, PEG-IFN/RBV, DAAs, Latin America